Benson Relaxation Technique to Reduce Pain in Patients After Transurethral Resection of the Prostate - Fidya Anisa Firdaus; Argi Virgona (INDOGENIUS, 2026)
Background & Objective: Pain is a common complaint among patients after Transurethral Resection of the Prostate (TURP). One non-pharmacological method that can be used is Benson relaxation, a relaxation technique that combines deep breathing with a belief system or focused words to induce a relaxation response. The purpose of this article is to examine the effectiveness of Benson relaxation in reducing pain levels in post-TURP patients. Method: The method used is a review of the application of Benson relaxation in post-TURP patients through an evidence-based nursing approach. Benson relaxation was performed regularly during the post-operative period for 10–15 minutes. Result: The results showed a decrease in pain intensity experienced by patients after Benson relaxation compared to before the intervention. Patients also demonstrated a more relaxed response, decreased muscle tension, and increased comfort. Conclussions: Benson relaxation is effective as a non-pharmacological therapy in helping reduce pain in post-TURP patients and can be recommended as a complementary nursing intervention.